Phenotypic Characterization and Husbandry Practice of Indigenous Chicken Ecotypes at West Guji, Ethiopia - Hirbaye, Natae; Kumar , Shalu; Tesema , Birhanu; Dadacha , Diba (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study was conducted with the objectives of characterization of indigenous chicken ecotypes and their husbandry practice at West Guji. A total of 204 households were randomly selected from two purposively selected woredas and 612 mature chickens were used for qualitative and quantitative traits data collection. The collected data were analyzed using the Statistical Package for Social Sciences (SPSS Version, 20) and the General Linear Model procedure (PROC GLM) of SAS. The qualitative data of feather distribution, plumage color, beak color, eye color, comb types, earlobe color, head shape, and shank color were collected. The result showed a significant difference between the districts (P< 0.05). Further, wing span, chest circumstance, body weight, and body length quantitative data were also recorded. The result revealed that there was a significant difference in quantitative traits in the study areas (P< 0.05). Egg production potentials, body weight, plumage color, hatchability, growth rate, and mothering ability were traits preferred by the household for female selection. The average age at first egg laying of indigenous chicken was 6.69±0.36 months and the number of eggs per hen per clutch was 12.16±0.26. The current finding revealed that about 93.5% of the observed chicken’s ecotypes were feathered and 6.45% were naked necks. The dominant chicken’s plumage colors identified were; brownish (29.28%), red (24.05%), and multicolor/ambesma (14.65%). The production systems practiced in the study area were extensive. Finally, phenotypic characterization of indigenous chicken ecotypes and performance evaluation should be supported by genetic characterization methods.